Revision of recluse spiders (Araneae: Sicariidae: Loxosceles) preserved in Dominican amber and a totalevidence phylogeny of Scytodoidea reveal the first fossil Drymusidae - Fiorini de Magalhaes, Ivan Luiz (2022)
Recluse or violin spiders in the genus Loxosceles (Scytodoidea: Sicariidae) are a diverse group (~140 extant species) including medically important species and distributed mainly in the Americas, Africa, and the Mediterranean region. In addition, this genus includes three fossil species from Miocene Dominican amber. Here we revise the taxonomy of these fossil species by examining, imaging and re-describing their type specimens. We find that L. defecta Wunderlich, 1988 and L. deformis Wunderlich, 1988 are bona fide members of the genus and report additional characters overlooked in their original descriptions. We further study the holotype of L. aculicaput Wunderlich, 2004 using synchrotron radiation micro-computed tomography to reveal previously unknown morphological details hidden by fissures in the amber. We found several characters inconsistent with Loxosceles but consistent with Drymusa (false violin spiders; Scytodoidea: Drymusidae), such as three claws, well-developed podotarsite, and a broad colulus. This suggests the species is misplaced in Loxosceles. To test this hypothesis, we estimated a total-evidence phylogeny of the superfamily Scytodoidea including extant and fossil taxa, morphological data, traditional molecular markers, and sequences of ultra-conserved elements. The results show unambiguously that L. aculicaput belongs to Drymusa and is a close relative of extant species of the genus inhabiting the Greater Antilles. Therefore, we here transfer this species to Drymusa, establishing a new combination and new family assignment. Drymusa aculicaput comb. nov. represents the first known fossil Drymusidae and shows that crown members of this genus already existed in the Miocene.